Identity Crisis - Common Tumors in Exceptional Locations, A Case Series - Rajendran Thilaga; Palanisamy Vanitha; Vasavan Yabitha; Shanmuganathan Jothi (Journal of Public Health International, 2020)
Mucoepidermoid carcinoma (MEC) accounts for only 5% of all salivary gland tumors and is most often seen in the parotid glands. MEC occurrence in the larynx is, however, rare. The incidence of primary squamous cell carcinoma (SCC) of salivary glands is also scarce and comprises only about 1.6% of all salivary gland malignancies. Hereby, we share our experience in managing two patients with rare and opposite variants of malignancy which were diagnosed at the same time; MEC of the larynx and SCC of the parotid. In MEC tumors, the presence of the intermediate and mucous cells with positivity in mucicarmine stain are the significant features. For SCC tumors, identification of the usual tumor markers (p40, CK 5/6 and p63) are pathognomonic. Although MEC and SCC are common in the head and neck regions, the existence of these malignancies in exceptional locations must be considered. The key features mentioned in our comparison table can help distinguish both these tumors and to deliver the correct treatment modalities. The prevalence of genomic and carcinogenic factors in the occurrence of these tumors in uncommon locations needs to be explored in future studies.
Keywords: Immigration